Bandgap‐Coupled Template Autocatalysis toward the Growth of High‐Purity sp2 Nanocarbons. Issue 7 (18th February 2021) - Gao, Jun; Zhu, Zhenxing; Shen, Boyuan; Bai, Yunxiang; Sun, Silei; Wei, Fei
Abstract: Extraordinary properties and great application potentials of carbon nanotubes (CNT) and graphene fundamentally rely on their large‐scale perfect sp 2 structure. Particularly for high‐end applications, ultralow defect density and ultrahigh selectivity are prerequisites, for which metal‐catalyzed chemical vapor deposition (CVD) is the most promising approach. Due to their structure and peculiarity, CNTs and graphene can themselves provide growth templates and nonlocal dual conductance, serving as template autocatalysts with tunable bandgap during the CVD. However, current growth kinetics models all focus on the external factors and edges. Here, the growth kinetics of sp 2 nanocarbons is elaborated from the perspective of template autocatalysis and holistic electronic structure. After reviewing current growth kinetics, various representative works involving CVD growth of different sp 2 nanocarbons are analyzed, to reveal their bandgap‐coupled kinetics and resulting selective synthesis. Recent progress is then reviewed, which has demonstrated the interlocking between the atomic assembly rate and bandgap of CNTs, with an explicit volcano dependence whose peak would be determined by the environment. In addition, the topological protection for perfect sp 2 structure and the defect‐induced perturbation for the interlocking are discussed. Finally, the prospects for the kinetic selective growth of perfect nanocarbons are proposed. Abstract : The developments toward perfect nanocarbon structures are presented, and the importance of bandgap‐coupled template autocatalysis kinetics is emphatically demonstrated. The protection provided by large formation energies of topological defects for perfect sp 2 structure is revealed. Furthermore, the bandgap‐coupled autocatalysis growth kinetics, which could modulate detailed structure of nanocarbons due to their slight difference in bandgap, are manifested by various evidences.